Combined bulk-rock Hf- and Nd-isotope compositions of Mesoarchaean metavolcanic rocks from the Ivisaartoq Supracrustal Belt, SW Greenland: Deviations from the mantle array caused by crustal recycling - Polat, Ali (Geochemistry, 2016)
Bulk-rock Lu-Hf and Sm-Nd isotope compositions, as well as major and trace element data are presented for metavolcanic rocks from the Mesoarchaean (ca. 3075 Ma) Ivisaartoq Supracrustal Belt in the Nuuk region of southern West Greenland. The εHft calculated at 3075 Ma range from +0.8 to +3.1 and the corresponding εNdt values range from +0.7 to +3.6, which forms an array that is displaced off the mantle array for these two isotopic systems. Primitive mantle normalized trace element plots of the metabasalts display negative Nb- and Ti-anomalies in combination with the elevated Th abundances, which is consistent with a subduction zone affinity as proposed by previous studies of this metavolcanic belt. No significant correlations are observed between the isotope compositions and proxies of shallow crustal contamination in the Ivisaartoq rocks, despite clear evidence for inherited Eoarchaean zircon (Polat et al., 2009. Chemical Geology 268, 248-271) which would have dominated the bulk-rock Hf-isotope budget. Furthermore, the measured samples are less radiogenic than the estimate for the depleted mantle composition at 3075 Ma. The lack of isotope and trace element correlation suggests incomplete equilibration between the crustal contaminant and the parental Ivisaartoq melts. We prefer a petrogenetic model with some combination of slab-derived metasomatism of the mantle source region for the Ivisaartoq magmas, which homogenized their trace element contents, in combination with the incorporation of granitoid restite with unradiogenic Hf-isotope composition at higher degrees of partial melting and finally the eruption of mechanically entrained Eoarchaean crust without significant chemical equilibration. The geochemical arc-affinity and non-DM isotope compositions of these metavolcanic rocks support the notion that crustal recycling and plate tectonics has been operating on Earth since at least the Mesoarchaean Eon.